Financial inclusion, demographics, and experiential learning as drivers of entrepreneurial intention among Generation Z - Umiyati, Etik; Hastuti, Dwi; Kusuma Edy, Jaya (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2025)
In the contemporary digital economy, entrepreneurial development has become a crucial factor in strengthening national competitiveness. Higher education institutions are therefore expected to cultivate entrepreneurial capacity among students, particularly those from Generation Z, who face increasingly dynamic economic challenges. This study aims to analyze the effects of financial literacy, financial inclusion, and demographic factors on entrepreneurship and entrepreneurial intention. The study employed a quantitative approach using survey data collected from students of the Faculty of Economics and Business at Universitas Jambi. The data were analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method. The results indicate that financial inclusion has a significant positive effect on both entrepreneurship and entrepreneurial intention, while demographic factors significantly influence entrepreneurship but do not directly affect entrepreneurial intention. Entrepreneurship itself exerts a strong, significant effect on entrepreneurial intention, suggesting that entrepreneurial engagement serves as the primary pathway through which background characteristics and access to financial services are translated into entrepreneurial intention. In contrast, financial literacy does not show a significant direct effect on either entrepreneurship or entrepreneurial intention. These findings highlight that access to financial services and experiential entrepreneurial engagement are more decisive than financial knowledge alone in fostering entrepreneurial intention among Generation Z students, implying that universities should prioritize practice-based entrepreneurship education supported by inclusive financial access.